Enzymatic carbon dioxide to formate: Mechanisms, challenges and opportunities. (May 2023) - Chen, Han; Huang, Yu; Sha, Chong; Moradian, Jamile Mohammadi; Yong, Yang-Chun; Fang, Zhen
Abstract: The reduction of carbon dioxide (CO2 ) gas into soluble formate is one of the most promising carbon neutralization strategies since it facilitates simultaneous fixation of carbon dioxide and the production of green chemicals. Compared to processes using chemical catalysts, enzymatic CO2 -to-formate is attractive due to its high efficiency, excellent selectivity, and mild conditions. This review summarizes different CO2 -to-formate enzymes, including formate dehydrogenase (FDH), hydrogen-dependent CO2 reductase and nitrogenase, as well as reduced nicotinamide adenine dinucleotide (NADH)-dependent and NADH-independent catalytic mechanisms. The challenges for enzymatic catalysis include high-cost sacrificial donors and low NADH regeneration efficiency. New photochemical and electrochemical NADH regeneration methods and advanced NADH-independent systems provide new opportunities to overcome these challenges. Harnessing artificial electroactive mediators and diffusive-cofactor-free systems enable more feasible and sustainable enzymatic CO2 -to-formate processes. Based on the versatile performance of enzymatic catalysis, there is potential for emerging applications such as upgrading carbon through multi-enzyme cascades and whole-cell catalysis. Bulk chemical biorefineries based on formate and using CO2 as a feedstock may be possible through from FDH-containing and engineered bacteria. Highlights: Enzymatic CO2 reduction to formate is a sustainable method for carbon neutralization. The electron transfer into enzyme step decides the efficiency of CO2 -to-formate. The abiotic-biotic interface enhances NADH regeneration and formate biosynthesis. Photochemical and electrochemical process are renewable to drive enzyme catalysis. Enzymatic CO2 -to-formate augments the ability of whole cells to upgrade carbon.